Microalbuminuria in nondiabetic patients with nonalcoholic fatty liver disease: association with liver fibrosis - ÇELİKEL, ÇİĞDEM; DUMAN, DENİZ; ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF (W B SAUNDERS CO-ELSEVIER INC, 2010)
Recent evidence has suggested an association between microalbuminuria and ultrasound-diagnosed nonalcoholic fatty liver disease (NAFLD) in patients with diabetes and prediabetes However, few data are available on the occurrence of microalbuminuria in nondiabetic subjects with histologically proven NAFLD We thus evaluated the relationships between microalbuminuria and liver histology in a hospital-based sample of 87 adults with biopsy-proven NAFLD from Turkey An albumin excretion rate less than 30 mg/d was considered within the reference range, whereas an albumin excretion rate from 30 to 300 mg/d was considered to indicate microalbuminuria Compared with those without microalbuminuria (n = 73), NAFLD patients with microalbuminuria (n = 14) had significantly higher homeostasis model assessment of insulin resistance values (3 9 +/- 1 3 vs 5 8 +/- 3 7, P < 001) There were no differences in the prevalence of microalbuminuria in patients with definite nonalcoholic steatohepatitis, borderline nonalcoholic steatohepatitis, and simple fatty liver In the entire study cohort, mean fibrosis scores were significantly higher in patients with microalbuminuria than in those without (1 27 +/- 0.26 vs 0 80 +/- 0 11, P < 05) This difference persisted after adjustment for potential confounders These results indicate the presence of a significant association between the seventy of insulin resistance and microalbuminuria in patients with NAFLD In addition, microalbuminuria may identify NAFLD patients with higher fibrosis scores (C) 2010 Elsevier Inc. All rights reserved
Keywords: CHRONIC KIDNEY-DISEASE; INSULIN-RESISTANCE; PROVISIONAL REPORT; METABOLIC SYNDROME; CONSULTATION; HYPERTENSION